Agama dan Ideologi - Donatus Sermada (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2008)
The description of the freedom of how to practice the religion in Indonesia as the author reflects on it in the light of the official documents is a stepping stone to go deeper into the important insight to the relationship between religion and ideology. The freedom of practicing the religion should be based on the correct understanding of the essential difference between religion and ideology. The author attempts to elaborate both of them separatedly in order to gain the genuine insight to the basic essential difference between them. The essence of religion is reflected in the line of tracing linguistic meaning of two words